Multi parametric model predictive control based on laguerre model for permanent magnet linear synchronous motors - Nguyen Hong Quang; Nguyen Phung Quang; Dao Phuong Nam; Nguyen Thanh Binh (Institute of Advanced Engineering and Science, 2019)
The permanent magnet linear motors are widely used in various industrial applications due to its advantages in comparisons with rotary motors such as mechanical durability and directly creating linear motions without gears or belts. The main difficulties of its control design are that the control performances include the tracking of position and velocity as well as guarantee limitations of the voltage control and its variation. In this work, a cascade control strategy including an inner and an outer loop is applied to synchronous linear motor. Particularly, an offline MPC controller based on MPP method and Laguerre model was proposed for inner loop and the outer controller was designed with the aid of nonlinear damping method. The numerical simulation was implemented to validate performance of the proposed controller under voltage input constraints.